Dietary Fibre Intake Is Associated with Serum Levels of Uraemic Toxins in Children with Chronic Kidney Disease - Amina El Amouri; Evelien Snauwaert; Aurélie Foulon; Charlotte Vande Moortel; Maria Van Dyck; Koen Van Hoeck; Nathalie Godefroid; Griet Glorieux; Wim Van Biesen; Johan Vande Walle; Ann Raes; Sunny Eloot (Toxins, 2021)
Imbalanced colonic microbial metabolism plays a pivotal role in generating protein-bound uraemic toxins (PBUTs), which accumulate with deteriorating kidney function and contribute to the uraemic burden of children with chronic kidney disease (CKD). Dietary choices impact the gut microbiome and metabolism. The aim of this study was to investigate the relation between dietary fibre and gut-derived PBUTs in paediatric CKD. Sixty-one (44 male) CKD children (9 ± 5 years) were prospectively followed for two years. Dietary fibre intake was evaluated by either 24-h recalls (73%) or 3-day food records (27%) at the same time of blood sampling for assessment of total and free serum levels of different PBUTs using liquid chromatography. We used linear mixed models to assess associations between fibre intake and PBUT levels. We found an inverse association between increase in fibre consumption (g/day) and serum concentrations of free indoxyl sulfate (−3.1% (−5.9%; −0.3%) (p = 0.035)), free p-cresyl sulfate (−2.5% (−4.7%; −0.3%) (p = 0.034)), total indole acetic acid (IAA) (−1.6% (−3.0%; −0.3%) (p = 0.020)), free IAA (−6.6% (−9.3%; −3.7%) (p < 0.001)), total serum p-cresyl glucuronide (pCG) (−3.0% (−5.6%; −0.5%) (p = 0.021)) and free pCG levels (−3.3% (−5.8%; −0.8%) (p = 0.010)). The observed associations between dietary fibre intake and the investigated PBUTs highlight potential benefits of fibre intake for the paediatric CKD population. The present observational findings should inform and guide adaptations of dietary prescriptions in children with CKD.